637 Prenatal Exposure to Hydroxylated Polychlorinated Biphenyls is Associated with the Quality of the Motor Repertoire in Three-Month-Old Infants. (October 2012) - Berghuis, SA; Soechitram, SD; Hitzert, MM; Sauer, PJJ; Bos, AF
Abstract : Background and Aim: Polychlorinated biphenyls (PCBs) are ubiquitous environmental toxins, potentially toxic to the developing brain. Hydroxylated PCBs (OH-PCBs) are suggested to be even more toxic because of hydroxylation by the fetus and active transplacental transport of OH-PCBs. Still, little is known about their short-term health effects in humans. We aimed to determine whether prenatal exposure to OH-PCBs is associated with the neurological condition in three-month-old infants, assessed by the quality of the motor repertoire. Methods: In a Dutch observational cohort study, 97 mother-infant pairs participated. Cord blood samples were analyzed for PCB and OH-PCB concentrations. The quality of the motor repertoire was evaluated at 3 months from video-recordings. We determined the quality of General Movements (GMs) and calculated a Motor Optimality Score (MOS) ranging from 5 to 28 (low to high optimality). We explored correlations between PCB/OH-PCB levels and MOS using Spearman's Rank correlation. Next, we tested whether PCB/OH-PCBs levels differed between infants with 'low' (<26) and 'high' MOS (≥26). Results: We found no association between PCB/OH-PCB levels and the quality of GMs. Associations existed between several PCB/OH-PCB levels and MOS, including detailed aspects of the motor repertoire. High 4-OH-PCB-107 levels were associated with a low MOS ( P =0.013). High PCB-187 levels were associated with reduced midline arm and leg movements ( P =0.047 and P =0.043, respectively). Conclusion: Prenatal exposure to higher 4-OH-PCB-107 levels was associated with a non-optimal quality of the motor repertoire in three-month-old infants. This negative effect may be mediated by reduced thyroid hormone concentrations in the brain.